Pleiotropic Roles of ChSat4 in Asexual Development, Cell Wall Integrity Maintenance, and Pathogenicity in Colletotrichum higginsianum - Yang, Ji-Yun; Fang, Yu-Lan; Wang, Ping; Ye, Jian-Ren; Huang, Lin (Frontiers in Microbiology, 2018)
Potassium has important roles in multiple cellular processes. In Saccharomyces cerevisiae, the serine/threonine (S/T) kinase Sat4/Hal4 is required for potassium accumulation, and regulates the resistance to sodium salts, and stabilization of other plasma membrane transporters. However, the functions of Sat4 in filamentous phytopathogenic fungi are largely unknown. In this study, ChSat4, the yeast Sat4p homolog in Colletotrichum higginsianum, was identified. Target deletion of ChSat4 resulted in defects in mycelial growth and conidiation. Intracellular K+ accumulation was significantly decreased in the ChSat4 deletion mutant. Additionally, the ΔChSat4 mutant showed defects in cell wall integrity, hyperoxide stress response, and pathogenicity. Localization pattern analysis indicated ChSAT4 was localized in the cytoplasm. Furthermore, ChSAT4 showed high functional conservation with the homolog FgSAT4 in Fusarium graminearum. Taken together, our data indicates that ChSat4 is important for intracellular K+ accumulation and infection morphogenesis in C. higginsianum.